2016
DOI: 10.1007/s10763-016-9752-8
|View full text |Cite
|
Sign up to set email alerts
|

Being a Mathematics Teacher Educator in China: Challenges and Strategic Responses

Abstract: In this exploratory study, we developed a portrait of the challenges and strategic responses of secondary mathematics teacher educators (MTEs) in Chinese universities. The MTEs reported encountering more challenges when teaching pedagogical courses and supervising student teachers than when teaching college mathematics courses and teaching mathematical problem-solving courses. This finding reflects a key difference between the content, goals, and teaching demands of these 2 elements of mathematics teacher educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For another, quantitative methods also make it possible to statistically measure and systematically compare research subjects across different content areas (Hesse-Biber & Johnson, 2015). When it comes to the subjects of studies, the majority of previous qualitative studies have targeted at teachers rather than students (Keiler, 2018;Wu & Cai, 2017;Yandell, 2017;Yadav et al, 2016). The present study holds that students, as the object of teaching and the subject of learning, constitute an indispensable part of classroom teaching and cannot afford to be neglected.…”
Section: Previous Studies In the Fieldmentioning
confidence: 83%
See 2 more Smart Citations
“…For another, quantitative methods also make it possible to statistically measure and systematically compare research subjects across different content areas (Hesse-Biber & Johnson, 2015). When it comes to the subjects of studies, the majority of previous qualitative studies have targeted at teachers rather than students (Keiler, 2018;Wu & Cai, 2017;Yandell, 2017;Yadav et al, 2016). The present study holds that students, as the object of teaching and the subject of learning, constitute an indispensable part of classroom teaching and cannot afford to be neglected.…”
Section: Previous Studies In the Fieldmentioning
confidence: 83%
“…Owning to the nature of qualitative research, the investigation methods are mainly case study, open-ended survey questions, interviews or classroom observations (Yandell, 2017;Lai et al, 2015). Additionally, the sample sizes of qualitative studies are mostly less than 10, with a few exceptions reaching 68 (Wu et al, 2017), 103 (Huang, 2017;Wan et al, 2011), 153 (Huang, 2019) or 324 (Killinc, 2017) The smaller sample sizes, combined with qualitative research methods, serve to pinpoint unique features of teacher roles pertaining to certain particular circumstances and provide in-depth insights into the relevant areas. However, qualitative research has its own limitation and it is considered to be more difficult to generalize their findings in other contexts.…”
Section: Previous Studies In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…A few other studies examined the challenges and the development of mathematics educators in China. Wu et al (2016) identified the challenges of being a mathematics teacher educator (university-based) and explored strategies for overcoming the challenges. By extending, Zaslavsky's (2008) model to include research lesson mediation objects, Huang et al (2014) investigated how MTRS and teachers co-learn through the reiterative cycles of lesson study.…”
Section: Development Of Mathematics Teacher-educators' Knowledge and Competencementioning
confidence: 99%
“…In recent years, the scientific community has been very interested in understanding the complexities of mathematics teaching and the didactic-mathematical knowledge that teachers need, either in general or specific topics. Results of these investigations have had a direct impact on the teacher training programs as a key point for educational improvement (Ponte & Chapman, 2008;Norton & Zhang, 2018;Stylianides, Stylianides, & Shilling-Traina, 2013;Wu, Hwang, & Cai, 2017).…”
Section: Introductionmentioning
confidence: 99%